2021
DOI: 10.1002/acm2.13239
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric feasibility of stereotactic ablative radiotherapy in pulmonary vein isolation for atrial fibrillation using intensity‐modulated proton therapy

Abstract: Purpose: To evaluate dosimetric properties of intensity-modulated proton therapy (IMPT) for simulated treatment planning in patients with atrial fibrillation (AF) targeting left atrial-pulmonary vein junction (LA-PVJ), in comparison with volumetric-modulated arc therapy (VMAT) and helical tomotherapy (TOMO).Methods: Ten thoracic 4D-CT scans with respiratory motion and one with cardiac motion were used for the study. Ten respiratory 4D-CTs were planned with VMAT, TOMO, and IMPT for simulated AF. Targets at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 65 publications
(148 reference statements)
0
5
0
Order By: Relevance
“…Four studies focused on PBT, and carbon ions were used in all cases: 2 works were dosimetric ( 58 , 59 ) and one reported on in vivo dosimetry on animals ( 60 ). The last one ( 61 ) compared intensity-modulated proton therapy with XRT delivered through VMAT and helical tomotherapy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four studies focused on PBT, and carbon ions were used in all cases: 2 works were dosimetric ( 58 , 59 ) and one reported on in vivo dosimetry on animals ( 60 ). The last one ( 61 ) compared intensity-modulated proton therapy with XRT delivered through VMAT and helical tomotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…The most recent article included on PBT, Ren et al ( 61 ), evaluated dosimetric properties of intensity-modulated proton therapy in comparison with VMAT and tomotherapy treatment planning; the prescription dose was 25 Gy in all plans. The proton-based technique resulted in a significantly reduce dose in surrounding tissues, compared to photon-based ones, in patients with AF.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A feasibility study using SABR to treat AF suggested this approach is effective and safe (35). As arrhythmogenic foci are commonly found at multiple PV-LA junctions in AF, invasive radiofrequency ablations typically involve the entire PV region, which has been shown to be feasible with SABR fields in a multimodality planning study (36). A phase II clinical trial testing uniform treatment to all four PV regions has recently launched and will provide preliminary safety and efficacy signals (37).…”
Section: Discussionmentioning
confidence: 99%